Research on Fire Resistance of Ultra-High-Performance Concrete - Hao-wen Ye; Nai-qian Feng; Yan Ling-hu; Zhi-wei Ran; Li-xun Lin; Shi-kun Qi; Yi Dong (Advances in Materials Science and Engineering)
Fire resistance of ultrahigh-performance concrete was measured under different temperatures and loadings. C120 concrete was prepared with 1 kg/m3 organic fiber and C120 concrete with 2 kg/m3 organic fiber and tested under loading at 30% ultimate strength when exposed to high temperatures of 200°C, 300°C, and 400°C, respectively.